The Great Story and the Great Bommission : Participating in the Biblical Drama of Mission - Wright, Christopher J. H., 1947- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2023)
"A highly-regarded scholar and speaker offers a succinct treatment of the Bible's grand narrative and how this influences believers' understanding of their mission in the world"--
A missional hermeneutic of scripture -- The great story as a drama in seven acts -- What does the great story do? -- The great commission and the five marks of mission -- Building the church through evangelism and teaching -- Serving society through compassion and justice -- The goodness and glory of creation -- The goal of creation -- The great story, the great commission, and the church's mission.
Includes bibliographical references and index.
Keywords: Mission of the church -- Biblical teaching; Great Commission; Missions - Biblical Teaching